Multiple coronary-cameral fistulas to the left ventricle arising from both coronary arteries - Ranjan Pathak; Smith Giri; Inyong Hwang; Shadwan Alsafwah (Greater Baltimore Medical Center, 2016)
Coronary-cameral fistula (CCF) is an anomalous connection between a coronary artery and a cardiac chamber or major vessel, seen in about 0.8% of the cases undergoing coronary angiography. Most patients are asymptomatic and diagnosis is made incidentally during coronary angiography. We present an image case of CCF which was found incidentally during pre-liver transplantation work up.